First case of ranavirus-associated mass mortality in a natural population of the Huanren frog (Rana huanrenensis) tadpoles in South Korea. Issue 5 (3rd September 2017) - Kwon, Sera; Park, Jaejin; Choi, Woo-Jin; Koo, Kyo-Soung; Lee, Jin-Gu; Park, Daesik
ABSTRACT: Globally, ranavirus is often responsible for the mass mortality of a variety of captive and wild amphibians. In Asia, several mass mortality cases of captive amphibians by ranavirus are known, but one mass mortality case in the wild has been reported in a non-endemic larval bullfrog population in Japan. In order to verify factors involved in mass mortality of Rana huanrenensis tadpoles (> 200 tadpoles) in a mountain stream in South Korea, we investigated possible infections by ranavirus, chytrid fungus, and lethal bacteria by conducting PCR assays of pathogens with specific primers. We found that all R. huanrenensis tadpoles collected (two alive and ten carcasses) showed positive PCR results for two different ranavirus primer sets targeting partial genes of a major capsid protein (MCP). The identified MCP sequence was more closely related to Rana catesbeiana virus JP MCP, isolated from invasive bullfrog tadpoles in Japan. We could not detect any lethal bacteria or chytrid fungus in the specimens. Our finding is the first report in Asia that ranavirus is involved in the mass mortality of endemic wild amphibians.